Probing the impact of varied migration and gas accretion rates for the formation of giant planets in the pebble accretion scenario - Ndugu, N; Bitsch, B; Morbidelli, A; Crida, A; Jurua, E (Monthly Notices of the Royal Astronomical Society, 2020)
The final orbital position of growing planets is determined by their migration speed, which is essentially set by the planetary mass. Small mass planets migrate in type-I migration, while more massive planets migrate in type-II migration, which is thought to depend mostly on the viscous evolution rate of the disc. A planet is most vulnerable to inward migration before it reaches type-II migration and can lose a significant fraction of its semimajor axis at this stage. We investigated the influence of different disc viscosities, the dynamical torque, and gas accretion from within the horseshoe region as mechanisms for slowing down planet migration. Our study confirms that planets growing in low viscosity environments migrate less, due to the earlier gap opening and slower type-II migration rate. We find that taking the gas accretion from the horseshoe region into account allows an earlier gap opening and this results in less inward migration of growing planets. Furthermore, this effect increases the planetary mass compared to simulations that do not take the effect of gas accretion from the horseshoe region. Moreover, combining the effect of the dynamical torque with the effect of gas accretion from the horseshoe region, significantly slows down inward migration. Taking these effects into account could allow the formation of cold Jupiters (a > 1 au) closer to the water ice line region compared to previous simulations that did not take these effects into account. We, thus, conclude that gas accretion from within the horseshoe region and the dynamical torque play crucial roles in shaping planetary systems.
Keywords: Accretion; Accretion discs; Planet-disc interaction; Protoplanetary discs; Planetary systems.